Melastrongygaster, a new genus of the tribe Strongygastrini (Diptera: Tachinidae), with five new species from Asia - Shima, Hiroshi (Zootaxa, 2015)
A new genus with five new species of the Tachinidae is described: Melastrongygaster gen. nov., M. atrata sp. nov. (type species) from Japan and South Korea, M. chaoi sp. nov. from China, M. fuscata sp. nov. from China, M. kambaitiana sp. nov. from Myanmar and M. orbitalis sp. nov. from Vietnam. Melastrongygaster belongs to the tribe Strongygastrini and the subfamilial position of the tribe is discussed.